Use of Impella Ventricular Assist Device in Patients with Severe Coronary Artery Disease Presenting with Cardiac Arrest - Mukku, Venkata K.; Cai, Qiangjun; Gilani, Syed; Fujise, Ken; Barbagelata, Alejandro (International Journal of Angiology, 2012)
Impella (Abiomed, Danvers, MA) is a percutaneously inserted ventricular assist device (VAD). It has been increasingly used in patients with severe heart failure, cardiogenic shock, and high-risk percutaneous intervention (PCI). However, the use and efficacy of Impella in patients with severe coronary artery disease (CAD) presenting with cardiac arrest has rarely been reported.The objective of this study is to report our center experience in using Impella VAD in CAD patients presenting with cardiac arrest. From December 2010 to March 2011, three patients with severe CAD presented to our center with cardiac arrest underwent PCI with Impella support. We reported three cases of severe CAD presenting with cardiac arrest successfully treated with PCI and Impella support. Our experience demonstrated that Impella VAD may play an adjunctive role in obtaining hemodynamic stability in these high-risk patients undergoing PCI. One of the patients was supported to left VAD implantation, and the other two had excellent neurological and functional recovery. Our reports suggest an important role of Impella in cardiac arrest population. Earlier Impella implantation after cardiac arrest might provide cardiac support and tissue perfusion until recovery or high-risk PCI.
Keywords: ventricular assist devices; coronary artery disease; percutaneous coronary intervention; ST segment elevation myocardial infarction; cardiopulmonary resuscitation; cardiac; catheterization; intra-aortic balloon pump